How useful is the machine perfusion in liver transplantation? An answer from a national survey - Scalera, Irene; De Carlis, R.; Patrono, D.; Gringeri, E.; Olivieri, T.; Pagano, D.; Lai, Q.; Rossi, M.; Gruttadauria, S.; Di Benedetto, F.; Cillo, U.; Romagnoli, R.; et al. (Frontiers in Surgery, 2022)
Machine perfusion (MP) has been shown worldwide to offer many advantages in liver transplantation, but it still has some grey areas. The purpose of the study is to evaluate the donor risk factors of grafts, perfused with any MP, that might predict an ineffective MP setting and those would trigger post-transplant EAD. Data from donors of all MP-perfused grafts at 6 liver transplant centers have been analyzed, whether implanted or discarded after perfusion. The first endpoint was the negative events after perfusion (NegE), that is the number of grafts discarded plus those were implanted but lost after the transplant. A risk factor analysis for NegE was performed and marginal grafts for MP were identified. Finally, the risk of EAD was analyzed, considering only implanted grafts. From 2015 to September 2019, 158 grafts were perfused with MP: 151 grafts were implanted and 7 discarded after the MP phase because they did not reach viability criteria. Of 151, 15 grafts were lost after transplant, so, the NegE group consisted of 22 donors. In univariate analysis, the donor risk index >1.7, presence of hypertension in the past medical history, S-CIT and the moderate or severe macro-vesicular steatosis were the significant factors for NegE. Multivariate analysis confirmed the macro-steatosis> 30% was an independent risk factor for NegE (odd ratio 5.643, p=0.023, 95%CI: 1.27-24.98). Of 151 transplanted patients 34% of recipients experienced EAD and had worse 1- & 3-year-survival, compared with those who did not faced EAD (NoEAD), 96% & 96% for EAD versus 89% & 71% for NoEAD, respectively (p=0.03). None of the donor/graft characteristics was associated to EAD even if the graft was moderately steatotic or fibrotic or from an aged donor. For the first time, this study shows that macro vesicular steatosis > 30% might be a warning factor involved in the risk of graft loss or a cause of graft discard after the MP treatment. On the other hand, the MP seems to be useful in reducing the donor and graft weight in development an EAD.